2004
DOI: 10.1103/physrevlett.93.048103
|View full text |Cite
|
Sign up to set email alerts
|

HDesorption from Uracil via Metastable Electron Capture

Abstract: In this Letter we report an analysis of the quantum dynamics for the scattering of slow electrons off uracil molecules, leading to the formation of a trapped, metastable anionic state at around 9 eV of energy. This resonant state is seen to be capable of describing an anionic molecular precursor which can explain the desorption of the H- species observed in experiments on film deposited uracil samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…In addition to the poor characterization of the possible higher-lying resonances in pyrimidine DNA bases, previous studies [18][19][20][22][23][24][25] have struggled to produce parameters of, especially, the third (highest-lying) π * resonance in satisfactory agreement with experimental values. For this reason, Winstead and McKoy investigated elastic electron collisions with a model molecule, pyrazine.…”
Section: The Calculations Of Winstead and Mckoy Found Evidence Forsupporting
confidence: 65%
“…In addition to the poor characterization of the possible higher-lying resonances in pyrimidine DNA bases, previous studies [18][19][20][22][23][24][25] have struggled to produce parameters of, especially, the third (highest-lying) π * resonance in satisfactory agreement with experimental values. For this reason, Winstead and McKoy investigated elastic electron collisions with a model molecule, pyrazine.…”
Section: The Calculations Of Winstead and Mckoy Found Evidence Forsupporting
confidence: 65%
“…First, for shape resonances the lifetime is usually too short above 5 eV for dissociation [16,24] and electron detachment or transfer is highly probable. Second, Grandi et al [25] have reported the formation of a shape resonance for uracil near 9 eV. Consequently, this transient anionic state, which should also exist for nucleobases bound in DNA, could transfer its excess electron to unfilled orbitals of the phosphate group, lying close to 9 eV.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 99%
“…Gianturco and Lucchese 28 reported ‫ء‬ and ‫ء‬ shape-resonance energies determined from a scattering calculation; however, Burrow has questioned 29 the correctness of these results on both experimental and theoretical grounds. Grandi and co-workers 30 also reported a study of uracil at higher collision energies, ϳ9 eV, using a similar approach to that of Gianturco and Lucchese but with the further approximation of imposing D 2h symmetry on the scattering electron's wave function. Gianturco and Lucchese do not report cross sections, and Grandi and co-workers report only partial cross sections for some ͑D 2h ͒ symmetries.…”
Section: Introductionmentioning
confidence: 99%